Improvement of high-voltage staircase drive circuit waveform for high-intensity therapeutic ultrasound. (21st June 2016) - Tamano, Satoshi; Jimbo, Hayato; Azuma, Takashi; Yoshizawa, Shin; Fujiwara, Keisuke; Itani, Kazunori; Umemura, Shin-Ichiro
Abstract: Recently, in the treatment of diseases such as cancer, noninvasive or low-invasive modality, such as high-intensity focused ultrasound (HIFU), has been put into practice as an alternative to open surgery. HIFU induces thermal ablation of the target tissue to be treated. To improve the efficiency of HIFU, we have proposed a "triggered-HIFU" technique, which uses the combination of a short-duration, high-voltage transmission and a long-duration, medium-voltage transmission. In this method, the transmission device must endure high peak voltage for the former and the high time-average power for the latter. The triggered-HIFU sequence requires electronic scanning of the HIFU focus to maximize its thermal efficiency. Therefore, the transmission device must drive an array transducer with the number of elements on the order of a hundred or more, which requires that each part of the device that drives each element must be compact. The purpose of this work is to propose and construct such a transmission device by improving the staircase drive circuit, which we previously proposed. The main point of improvement is that both N and P MOSFETs are provided for each staircase voltage level instead of only one of them. Compared with the previous ultrasonic transmission circuit, high-voltage spikes were significantly reduced, the power consumption was decreased by 26.7%, and the transmission circuit temperature rise was decreased by 14.5 °C in the triggered-HIFU heating mode.